Congenital Diaphragmatic Hernia Diagnosed Postnatally Despite Prenatal Suspicion of Duodenal Atresia: A Case Report and Review of Perinatal Management Strategies (Bangladesh Journal of Medical Science, 2026)
Background Congenital diaphragmatic hernia (CDH) is a developmental malformation characterized by incomplete diaphragm formation and is associated with significant neonatal morbidity and mortality. Auxiliary imaging modalities, such as ultrasound and magnetic resonance imaging, as well as molecular studies, have improved both treatment and prognosis. However, atypical presentations may delay diagnosis and hinder perinatal care planning. Case Presentation We report the case of a term neonate who was prenatally suspected to have duodenal atresia and presented at birth with severe respiratory distress requiring immediate medical intervention. Initial stabilization included positive pressure ventilation, which led to progressive clinical deterioration. A chest radiograph performed shortly after birth revealed findings consistent with a left-sided Bochdalek hernia. The patient underwent prompt endotracheal intubation and surgical repair in a tertiary care center. Despite the extensive diaphragmatic defect, the clinical course was favorable, and the patient was discharged without complications 24 days later. Discussion: This case highlights the diagnostic challenges in prenatal imaging of CDH, particularly when other gastrointestinal anomalies are suspected. It underscores the importance of maintaining a broad differential diagnosis in cases of prenatal abdominal findings and supports the need for postnatal reevaluation when initial diagnoses are inconclusive. The favorable outcome in this patient was largely attributable to the availability of a multidisciplinary team and timely surgical intervention. Current literature supports that early referral to specialized centers and adherence to standardized ventilatory and surgical protocols are critical for improving survival in CDH. Conclusion This report reinforces the importance of high-resolution prenatal imaging, multidisciplinary perinatal planning, and early postnatal intervention in the management of CDH. Even in the absence of a definitive prenatal diagnosis, coordinated care in a specialized setting can significantly enhance outcomes. The findings contribute to clinical strategies for handling atypical CDH presentations and optimizing neonatal care pathways.BJMS, Vol. 25 No. 01 January’26 Page : 368-374